The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5045/br.2016.51.1.17
|View full text |Cite
|
Sign up to set email alerts
|

A scientific treatment approach for acute mast cell leukemia: using a strategy based on next-generation sequencing data

Abstract: BackgroundMast cell leukemia (MCL) is the most aggressive form of systemic mastocytosis disorders. Owing to its rarity, neither pathogenesis nor standard treatment is established for this orphan disease. Hence, we tried to treat a patient with MCL based on the exome and transcriptome sequencing results of the patient's own DNA and RNA.MethodsFirst, tumor DNA and RNA were extracted from bone marrow at the time of diagnosis. Germline DNA was extracted from the patient's saliva 45 days after induction chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In order to elucidate whether any of these mutated genes confers an adverse prognosis, multiple studies have been conducted in SM [11][12][13]29,32,68,80,90,120,160,176], from which a few include medium to large patient cohorts (n ≥ 100) [12,29,32,68,97]. Of note, the number of genes screened in these studies is highly variable, ranging from 9 genes [80] to 410 genes [13], with a few patients being investigated by whole-genome [13] or wholeexome [42,[177][178][179] sequencing. Overall, these studies found a total of 30 different genes to be mutated in SM (Table 2 and Table S1), from which 11 (i.e., ASXL1, CBL, DNMT3A, EZH2, JAK2, KRAS, NRAS, RUNX1, SF3B1, SRSF2, TET2) are recurrently mutated genes in several SM cohorts (Tables 3-5).…”
Section: Prognostic Impact Of Acquired Gene Mutations In Systemic Mas...mentioning
confidence: 99%
“…In order to elucidate whether any of these mutated genes confers an adverse prognosis, multiple studies have been conducted in SM [11][12][13]29,32,68,80,90,120,160,176], from which a few include medium to large patient cohorts (n ≥ 100) [12,29,32,68,97]. Of note, the number of genes screened in these studies is highly variable, ranging from 9 genes [80] to 410 genes [13], with a few patients being investigated by whole-genome [13] or wholeexome [42,[177][178][179] sequencing. Overall, these studies found a total of 30 different genes to be mutated in SM (Table 2 and Table S1), from which 11 (i.e., ASXL1, CBL, DNMT3A, EZH2, JAK2, KRAS, NRAS, RUNX1, SF3B1, SRSF2, TET2) are recurrently mutated genes in several SM cohorts (Tables 3-5).…”
Section: Prognostic Impact Of Acquired Gene Mutations In Systemic Mas...mentioning
confidence: 99%
“…Recent approaches such as next-generation sequencing will reveal even minor mutations or single nucleotide polymorphisms in neoplastic mast cells. In fact, Spector et al [30] and Youk et al [31] discovered a human mast cell leukemia-specific mutation in several genes. As the cost of these approaches decreases, they will be introduced in the veterinary field, probably leading to the deep understanding of mast cell tumorigenesis among species.…”
Section: Kit Mutation-independent Neoplastic Transformationmentioning
confidence: 99%
“…However, other mutations in SRSF2 , ASXL1 and/or RUNX1 have also been found in the patients with KIT D816V positive systemic mastocytosis, indicating that mutations in more than one gene may be necessary for leukemogenesis [ 5 6 ]. In this issue of the Blood Research , Youk et al [ 7 ] used next generation sequencing (NGS) to find mutations possibly causing the disease in a patient diagnosed with MCL. The whole exome sequencing revealed KIT S476I and whole transcriptome sequencing demonstrated possibly RARα-B2M fusion gene, and the authors used the results in personalized treatment.…”
mentioning
confidence: 99%